Recanalization of Proximal Fallopian Tube Obstruction in the Treatment of Infertility - Mody, Priya; Salazar, Gloria; Kohi, Maureen P. (Seminars in Interventional Radiology, 2023)
Infertility affects approximately 15% of patients worldwide, with up to 40% of cases attributed to tubal disease, and up to 25% of those being proximal fallopian tube obstruction (FTO). Evaluation of tubal patency can be performed via laparoscopic chromopertubation, hysterosalpingography, or hysterosalpingo-contrast-sonography (HyCoSy). In patients with proximal tubal obstruction, fallopian tube recanalization (FTR) can result in up to 100% technical success rate with pregnancy rates of 12.8 to 51%. More pregnancies occur when oil-soluble contrast media are used versus water-soluble contrast media. Complications of FTR are rare and include tubal perforation, ectopic pregnancy, and pelvic infection. Reocclusion of fallopian tubes may occur in 20 to 50% of patients; however, FTR may be repeated in these cases. Overall, FTR is underutilized in the treatment of infertility secondary to proximal FTO and it can obviate costly and time-consuming assistive reproductive techniques such as in vitro fertilization in some patients, as well as decreasing physical and emotional stress.
Keywords: fallopian tube occlusion; recanalization; tubal infertility; women's health; interventional radiology